DEVELOPMENT OF INTERNATIONAL LABOR COMMUNICATIONS IN THE GLOBAL LABOR MARKET SYSTEM - Trofanyuk , R. I. (The actual problems of regional economy development, 2024)
The globalization of the labor market has led to an increased need for international labor communications. This applies both to communication between employers and employees, and between different countries and international organizations. The purpose of the article is to conduct a study of Ukraine’s place in international labor communications and the global labor market system, as well as to determine aspects of external labor migration. To carry out the research, were used methods such as analysis, synthesis, systematization, generalization, formalization, etc. The scientific publication analyzes the place of Ukraine in international labor communications, being both an exporting country and an importing labor force. The advantages (increased income, decreased unemployment, acquisition of new skills, growth of gross domestic product and rapprochement with the EU) and challenges (migration of qualified personnel, social problems, danger of life) of Ukraine's participation in the global labor market system are explored. Based on the results of the study, theoretical aspects of external labor migration were identified, including economic, social and political aspects of the analysis and understanding of external labor migration, and proposals for the development of international labor communications in the global labor market system were formed. The scientific novelty of the article lies in the established proposals for the development of international labor communications in the global labor market system - strengthening cooperation between states, supporting the development of international trade unions, developing international platforms for job search, as well as strengthening the role of education and training for further practical use. The development of international labor communications is a fundamental factor in the development of the global labor market. This can lead to economic growth, improved living standards and increased cultural exchange. Governments and international organizations must take action to overcome the challenges to make the international labor market more accessible to all.